2008
DOI: 10.1017/s0266467408005002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative range use by three Atlantic Forest understorey bird species in relation to forest fragmentation

Abstract: Abstract:In this paper, we report on range use patterns of birds in relation to tropical forest fragmentation. Between 2003 and 2005, three understorey passerine species were radio-tracked in five locations of a fragmented and in two locations of a contiguous forest landscape on the Atlantic Plateau of São Paulo in south-eastern Brazil. Standardized ten-day home ranges of 55 individuals were used to determine influences of landscape pattern, season, species, sex and age. In addition, total observed home ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 40 publications
2
50
1
8
Order By: Relevance
“…If species do require specific nutrients found only in fruit resources, e.g. lipids, calcium, secondary metabolites (Bairlein 1996;O'Brien et al 1998;Bosque and Pacheco 2000;Tsahar et al 2003;Pierce and McWilliams 2004;Rode et al 2006), then as fruit resources become less available, or less consistently available, we should expect that species would either expand their home range size (Hansbauer et al 2008) thus decreasing population density or become locally extinct. In contrast, if species opportunistically consume fruits, then within human-altered land use types of structurally similar vegetation to forest (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If species do require specific nutrients found only in fruit resources, e.g. lipids, calcium, secondary metabolites (Bairlein 1996;O'Brien et al 1998;Bosque and Pacheco 2000;Tsahar et al 2003;Pierce and McWilliams 2004;Rode et al 2006), then as fruit resources become less available, or less consistently available, we should expect that species would either expand their home range size (Hansbauer et al 2008) thus decreasing population density or become locally extinct. In contrast, if species opportunistically consume fruits, then within human-altered land use types of structurally similar vegetation to forest (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Keel-billed Toucans, mean = 48 ha (Graham 2001a); White-throated Robins, mean = 26 ha (Cohen and Lindell 2005); Silver-throated Tanagers, mean = 16.7 ha (Sekercioglu et al 2007). However, only one study directly compared home range size between birds using the managed landscape versus undisturbed forest (Hansbauer et al 2008). Although Hansbauer et al (2008) evaluated three bird species in the heavily fragmented Brazilian Atlantic forest; the authors found that only the frugivorous species studied (Chiroxiphia caudata) displayed an increase in home range size in the fragmented forest: *12 ha in fragmented vs. *2 ha in undisturbed forest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As long as habitat resources are available, individuals may remain in their home patch, as movement is energy consuming and thus only a positive investment if the new patch provides an improved habitat quality (Robles & Ciudad 2012). Various studies have shown that smaller territories usually indicate higher habitat quality, while reduced habitat quality often leads to larger home ranges (Carey et al 1990, Hansbauer et al 2008. In addition, home-range sizes strongly depend on season most probably as a response on the availability of food resources (Wiktander et al 2001).…”
mentioning
confidence: 99%
“…Por outro lado, a eficiência do uso de indicadores formados por métricas da paisagem para identificar áreas com maior integridade da composição da comunidade gera uma grande perspectiva na aplicação Os dados obtidos para o projeto no qual esta tese se insere mostram que as mudanças nos habitats de Mata Atlântica causadas pela ação humana levam à perda de espécies de diversos táxons Bragagnolo et al, 2007;Umetsu & Pardini, 2007;Bueno, 2008;Naxara, 2008;Condez, 2008;Espartosa, 2009), perda de diversidade genética , redução na capacidade de imigração e emigração de indivíduos entre fragmentos (Uezu et al, 2005;Umetsu et al, 2008;Boscolo et al, 2008;Hansbauer et al, 2008a;Hansbauer et al, 2008b), entre outras alterações. Ou seja, o uso de métricas indicadoras parece ser a forma mais simples, rápida e prática de se avaliar a importância de áreas para a conservação considerando que: (i) as mudanças nos habitats naturais levam à perda de integridade das comunidades; (ii) amostragens de curta duração produzem resultados pouco consistentes; (iii) as mudanças nos habitats causadas pela ação humana são em geral fortemente correlacionadas (de forma que não é necessário medir todas as variáveis para se obter um bom poder explicativo); e (iv) que a obtenção de métricas da paisagem é muito mais fácil e rápida do que a condução de trabalho de campo para se obter dados biológicos.…”
Section: Quais São Os Melhores Indicadores Das Mudanças Na Integridadunclassified